Unravelling Anaesthetic Challenges in Neonate with Cavernous Haemangioma: A Case Report - Monika; Madhu; Urmi Malik; Neha; Sahil Shiva (Indian Journal of Neonatal Medicine and Research)
Haemangiomas are developmental vascular abnormalities characterised by hyperplasia of blood vessels, usually veins and capillaries. Haemangiomas show a higher prevalence in females. More than 50% of lesions are found in the head and neck region, with a particular preponderance over the face, lips, buccal mucosa, tongue, palate, and trunk. The aetiology can be neoplastic or reactive, influenced by factors such as hormones, infections, and trauma. Large lingual vascular malformations may present with obstructive symptoms, including difficulty in breathing, chewing, swallowing, and speech, which can lead to delays in linguistic development and compromised airway function. Haemangiomas are more susceptible to trauma, which can result in bleeding and further compromise the airway. Typically, this kind of presentation is managed conservatively until obstructive symptoms arise, at which point surgical removal or local site steroid instillation is considered. Here, a case of a 28-day-old child with a cavernous haemangioma of the tongue who was scheduled for excision and instillation of Kenacort injection at the base of the tongue has been reported. Due to the child’s small age and the presence of a lingual mass, the use of intravenous anaesthetic agents was precluded. In this case, because of the non-availability of a paediatric fibreoptic bronchoscope, blind nasal intubation was considered for securing the airway. Managing a compromised airway is a challenging situation, even for an experienced anaesthesiologist, in a routine operating room set-up. However, maintaining spontaneous ventilation is a crucial element during general anaesthesia.